RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN MENTIMUN (CUCUMIS SATIVUS L) YANG DITANAM PADA BEBERAPA UKURAN VOLUME MEDIA TANAM DALAM POLYBAG DENGAN TEKNIK IRIGASI TETES - Virsawan Paputungan; Leo H. Kalesaran; Ruland A. Rantung (Universitas Sam Ratulangi, 2023)
ABSTRACT This study aims to: 1. To measure the optimal amount of water use by the method of giving irrigation water, 2. To observe the relationship between the volume of planting media and the amount of irrigation water in cucumber plantations. This study was designed as an exploratory experimental research technique. Experiments were carried out on 5 polybag sizes/volume of planting media and each was repeated 3 times. The variables observed were the provision of water, number of leaves, number of fruit, fruit weight and shape of the root crown. The results of this study were 1. as much as 128,500 ml = 128.5 liters per plant, it turned out to be able to support and produce cucumber plants planted in polybags with the best production shown in experiments using 9 liter polybag sizes, 2. there was a positive response of plants to the treatment method drip irrigation and the amount of water given, and also showed a consistent relationship between plant vegetative growth (number of leaves) and the number and weight of fruit produced, namely the more leaves produced, the longer the roots and the width of the roots produced, the higher the number and the weight of the resulting fruit, where the highest production was achieved in the P5 treatment with an average number of 10 fruits/pot with a weight of 6,149 -6,354 kg. key words ; Cucumber, size of planting mediain polybag, drip irrigation.